IMPLIKASI HUKUM PELAKSANAAN PILKADA GUBERNUR DAN WAKIL GUBERNUR KALIMANTAN TENGAH - M. Rosyid Ridho (Al-Adl : Jurnal Hukum, 2025)
The exercise of people’s sovereignty in a direct democracy is realized through general elections including Regional Head Elections (Pilkada)’. As a critical agenda of a state governed by the rule of law, ‘the implementation of Regional Head Elections must adhere to a robust electoral system’.‘This study aims to analyze the legal implications of the postponed Central Kalimantan Governor and Deputy Governor Election originally scheduled for December 9, 2015 and subsequently held on January 27, 2016’. The analysis seeks to evaluate procedural compliance in the democratic process, particularly in the context of the Central Kalimantan Governor and Deputy Governor Election.‘This case highlights gaps in Indonesia’s Pilkada framework, especially in addressing unforeseen legal challenges, such as court-ordered postponements. It underscores the necessity for robust mechanisms to ensure legal certainty and public trust in Pilkada, which forms the foundation of Pancasila democracy.’ The research employs a normative juridical analysis method, examining relevant legislation and decisions of the General Election Commission (KPU), with a focus on the legal norms governing Pilkada in Indonesia. The study utilizes primary legal sources, namely ‘Law No 1 of 2015 and Law No 8 of 2015’. ‘Data were obtained from legal documents and regulations governing the implementation of Pilkada. The findings reveal that the KPU of the Republic of Indonesia and the Central Kalimantan Provincial KPU committed an unlawful act by failing to conduct the election on the designated date of December 9, 2015, and by scheduling a follow-up election on January 27, 2016, without a strong legal basis. These actions contravened the applicable legal provisions, specifically ‘Law No. 1 of 2015 and Law No. 8 of 2015’, ‘resulting in legal implications that render the implementation of the Central Kalimantan Governor and Deputy Governor Election unconstitutional, illegal, and an unlawful act (onrechtmatige daad)’.‘Consequently, the results of the election, including the determination of the winners, are deemed invalid or void (nietig) and subject to annulment’